Sistem Informasi Pemesanan Produk Percetakan Berbasis Web Menggunakan Metode Waterfall - Agung Izulhaq; Uce Indahyanti; Ika Ratna Indra Astutik (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Printing is an industry or service that serves the process of transferring designs in the form of text or images to print media using specialized machines. Jalanpintas.art is one of the printing service providers in Sidoarjo, but currently, they still operate manually. One of the frequent issues encountered is the inconvenience for customers in using the printing service, as they have to visit the physical location, which takes time, and then return to pick up the finished products on another day. Additionally, there are problems related to recording and calculation errors, document archiving, and time-consuming report generation. Therefore, the author has designed a web-based print product ordering information system with the aim of facilitating prospective customers in the ordering process and also serving as a promotional tool for Jalanpintas.art. The method used in this research is the Waterfall method. The Waterfall method is an approach in software development that consists of a series of steps, namely analysis, design, coding implementation, testing, and maintenance. The outcome of this research is the development of a web-based print product ordering information system. This system can be accessed and used by potential customers to place orders for print products